FLORA OF ANCIENT JAVA: IDENTIFICATION OF SPECIES, LANDSCAPE DISTRIBUTION, AND CULTURAL ASSOCIATION OF PLANTS MENTIONED IN OLD JAVANESE RAMAYANA - MULYANTO, DEDE; ISKANDAR, BUDIAWATI SUPANGKAT; ISKANDAR, JOHAN; WIYANTI, DEDE TRESNA (Research Center for Biology, 2024)
We searched the Old Javanese Ramayana as historical ethnobotanical resource and identified all references to plants and their biological references. Our analysis of plant names, landscape distributions, uses, and cultural associations in Java more than 1,000 years ago, includes trees and shrubs that appear in descriptions of landscapes, urban environments, forest hermitages, and uninhabited forested mountains. Of the 2,802 stanzas, only 198 stanzas (7.06%) mention plant names, with a total of 466 plant citations. Of all plant citations, we found 232 Old Javanese plant names, of which 230 had botanical references identified. These identified plant names refer to 204 spe-cies belonging to 76 plant families. The plant families with the most described species are Fabaceae (20 species), Po-aceae (11 species), and Moraceae (11 species). Of the 204 species identified, 114 are native to Java Island, 90 are non-native plants. Of the 232 Old Javanese plant names, 190 (81.89%) are of Javanese origin or have Proto-Austronesian or Proto-Malayo-Polynesian roots and show lexical similarity to the plant names in modern languages closely related to the Javanese. The plant species with the highest SDR value related to landscape description are the non-native plants Saraca asoca and Mangifera indica. The author of Old Javanese Ramayana not only knows the names of many plants and their uses, but also the characteristics of plants such as size, colour, taste, and habitat. The discovery con-firms previous scholar’s speculation that while the place names in the Old Javanese epics are Indian, the botanic ele-ments of these places is primarily Javanese